An exploratory study on awareness of waqf among Kenyan muslims - Mohammed, Abdi Shukur (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2017)
In Kenya, Waqf has been in practice since 1899 and played an important role in the Muslim society by providing social services for the community. Given such importance, the government went further to enact law which seemed amicable for the practice of Waqf by then. However, as time elapse the practice of Waqf declined and it became apparent that several factors undermined the potential of waqf in the socio-economic development of Muslims in Kenya, and this, has caught the attention of scholars to put on efforts to identify ways to revive Waqf in Kenya. These studies, however have been theoretical in nature. A pertinent aspect being considered was the Waqf Act and the management issues which most of them considered as an impediment to the development of Waqf in the country. There was also the issue of lack of awareness among most of the Muslims in Kenya about Waqf. Despite this, no detailed study has been conducted to investigate the issues, thus the novelty of this study is to investigate the knowledge level of Kenyan Muslims on Waqf and the role it plays in their awareness on Waqf. This study adopts quantitative method using structured questionnaire on a total number of 205 respondents. Most of the respondents came from two major cities in Kenya, namely Nairobi and Mombasa totaling 186 respondents, while the rests came from different counties of the country. The data was analyzed using Statistical Package for the Social Science (SPSS). The findings show that the respondents have ample knowledge about the general aspects of Waqf, while their knowledge on some specific characteristics of Waqf is quite low. Meanwhile, their awareness level of the current practice of Waqf is very low. The study has also found that there is a significant relationship between knowledge and awareness of Waqf among the respondents. Thus, it is advisable for the regulators as well as Muslim scholars to educate people about Waqf and its role in improving the well-being of the less fortunate segment of the society. This will increase the public awareness of Waqf, which will contribute to the revival of Waqf institution in the Kenya.